A stable solution-processed polymer semiconductor with record high-mobility for printed transistors - Ong, Beng S. (2013)
Microelectronic circuits/arrays produced via high-speed printing instead of traditional photolithographic processes offer an appealing approach to creating the long-sought after, low-cost, large-area flexible electronics. Foremost among critical enablers to propel this paradigm shift in manufacturing is a stable, solution-processable, high-performance semiconductor for printing functionally capable thin-film transistors — fundamental building blocks of microelectronics. We report herein the processing and optimisation of solution-processable polymer semiconductors for thin-film transistors, demonstrating very high field-effect mobility, high on/off ratio, and excellent shelf-life and operating stabilities under ambient conditions. Exceptionally high-gain inverters and functional ring oscillator devices on flexible substrates have been demonstrated. This optimised polymer semiconductor represents a significant progress in semiconductor development, dispelling prevalent skepticism surrounding practical usability of organic semiconductors for high-performance microelectronic devices, opening up application opportunities hitherto functionally or economically inaccessible with silicon technologies, and providing an excellent structural framework for fundamental studies of charge transport in organic systems.